Skeletal morphology and maturation of male Gambusia holbrooki exposed to sewage treatment plant effluent - Rawson, Christopher; Lim, R.; Warne, M. (Elsevier, 2008)
Sewage effluent has been identified as a major source of endocrine disrupting chemicals (EDCs) in the aquatic environment. The modified hemal spines (modified skeletal structures important in reproduction) of mosquitofish, Gambusia spp. have been shown to beunder androgenic control and to be affected by exposure to estrogen. The current study aimed to investigate the effects of two sewage treatment plants (STPs) in Sydney, Australia on the morphology of hemal spines in populations of Gambusia holbrooki and on the abilityof the fish to reach sexual maturity. The effluent from the two STPs had different effects on the hemal spines of males. At St. Marys differences in hemal spine morphology between fish upstream and downstream of the STP were not attributable to effluent from the STP.At Quakers Hill, results suggest that the effluent is generally estrogenic to G. holbrooki. There was a decrease in the proportion of males that were morphologically mature downstream of both STPs indicating potential population level effects that were associated with thepresence of the STPs.